PEMBUATAN MIKROENKAPSULASI BUAH NAGA MERAH (Hylocereus polyrhizus) DAN EVALUASI ANTIOKSIDANNYA - , RATNA DIAN ASTUTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Consuming food and beverages containing antioxidants is one of the efforts to prevent the occurrence of degenerative diseases. Red dragon fruit (Hylocereus polyrhizus), which is now known among public community, contains antioxidants and has benefits for health. However, red dragon fruit is one of the commodities that are easily damaged (perishable commodities). Therefore, as an alternative, red dragon fruit can be made in microencapsulated-powder. Objective: To know the differences in phenol total, vitamin C, and antioxidant activity contained on each microencapsulated-powder formula and to know the best microencapsulated-powder formula based on their color, aroma, and taste attribute Method: This study is an experimental study with complete random design. Red dragon fruit was extracted by using ethanol 70% (1 : 5). Later, the extract was microencapsulated by adding maltodextrin (15%, 20%, 25%), and then dried in a spray dryer. Variables which were analyzed on the red dragon fruit microencapsulated-powder are phenol total, vitamin C, antioxidant activity and the best formula based on the color, aroma, and taste of red dragon fruit microencapsulated-powder. Result: Based on the result of the ANOVA test (p < 0,05) showed that there is a true difference and a decrease in the total phenol, vitamin C, and antioxidant activity along with the addition of maltodextrin concentration on red dragon fruit microencapsulated-powder. For the ranking test result, the powder formula which has the highest rank on color attribute is the first formula which has mean rank 2,60, while the powder formula which has the highest rank on aroma and taste attribute is the second formula which has mean rank 2,27 and 2,34. Conclusion: Maltodextrin concentrations on powder formula will decrease the total phenol, vitamin C, and antioxidant activity in the powder. On the color attribute, the first formula get the highest point. While, on the aroma and taste attribute, the second formula get the highest point. Key words: red dragon fruit, microencapsulation, total phenol, vitamin C, antioxidant activity